For Brenda Dunne, Fond Memories and Deep Respect - Nelson, Roger D. (Journal of Scientific Exploration, 2022)
In early 1980, I answered a circumspect ad in the Chronicle of Higher Education looking for a “cognitive scientist interested in the lesser-known aspects of perception.” After some correspondence, I traveled from northern Vermont to Princeton to interview for a job that would, as I learned, touch on truly rarefied aspects of consciousness. By “accident,” I encountered Brenda walking down the hallway toward Bob Jahn's office, where I was headed for an interview, recognizing her though we had never met. It was quite a first impression—she was wearing a long flowing green dress and looked magical, and needless to say, obviously memorable. She was then and always a notable presence. The Princeton Engineering Anomalies Research (PEAR) lab was taking shape in the basement of Princeton University's School of Engineering, and from the beginning it had an unusually human quality because Brenda saw how important being at ease would be for people willing to try our experiments. She made the lab comfortable and home-like, installing the great orange couch with all its stuffed animals in PEAR's living room, and Comforto the Incredible chairs to coddle our operators as they attempted improbable tasks like intending that our Random Event Generator (REG) should produce high (or low) numbers on demand, or attempting to add some order (negentropy) to the Random Mechanical Cascade (RMC) or the big and beautiful but randomly arhythmic Native American drum. More important by far than the furniture was Brenda's presence in the lab. She was warm and genuinely interested in the people who came by, and many of them became long-term friends. Her easy confidence about the phenomena we studied was infectious, and that probably accounted for a large part of the success we had in demonstrating that the improbable could happen, and the impossible, too, though it might take longer. Brenda was clear that our studies were of phenomena, not people, and she invited the folks we called operators to relax and have fun with the experiments. She set a tone of collaboration, and rather than telling people how to work their will on the REG, she asked what they thought and felt. Some of the lab's most instructive findings come from what they had to say. Typically, our operators told us it was a matter of developing a relationship with the machine. “I began to feel loving connection.” Then the scores would climb.